The relationship of pod colour with the quality of Indigofera zollingeriana - Rijanto Hutasoit; . Riyadi; Juniar Sirait (Indonesian Center for Animal Research and Development (ICARD), 2019)
Indigofera zollingeriana (Indigofera) plant is potential feed ingredients. The propagation of this plant is through seed. The low quality of seed is a problem in its development. This study was aimed to evaluate the relationship of pod colour with quality of Indigofera seeds. The study was designed in a complete randomized design consisting of four pod colours and four replications, namely: P1= green, P2= brownish green, P3= brown, and P4= black. The parameters observed were: characteristic and morphology of pods and seeds of Indigofera, the growth of sprouts, and the growth of fungus on Indigofera seed. Results showed that the number of pests was fewest found in P2, brownish green pod (14%). The highest number of seeds was in P1, green pod (5173) and P2, brownish green pod (4944). The highest germination (62%) was detected in P2 (brownish green). The heaviest sprout was in P2, in brownish green pod (0.035g), highest sprout (2.68 cm) in P4, black pod colour. Based on fungus observation, the black pod (P4) provided the fewest result (6.63%), however most fungus grew very well in P1, the green pod (47.88%). It could be concluded that the brownish green pod colour was the best phase for harvesting good quality I. zolligeriana seed.